HBR's 10 must reads on negotiation (Harvard Business Review Press, 2019)
Learn how to be strategic and formidable in all aspects of negotiation--from reading the room, to staying cool, to achieving the best outcome. If you read nothing else on negotiation, read these 10 articles. We've combed through hundreds of Harvard Business Review articles and selected the most important ones to help you clinch successful deals in business and beyond. This book will inspire you to: Control the negotiation even before you enter the room Understand your counterpart's position and gain their trust Keep your negotiations from becoming confrontations Understand the rules of negotiating across cultures Find ways to expand the pie for all involved Set the stage for a healthy relationship after the ink has dried Know when to walk away from a deal.